Spanning Tree- Properties, Algorithms and Applications - Lakshmi, K; Meyyappan, T (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we present a survey of the spanning trees. The general properties of spanning trees, algorithms for generation of all possible spanning trees from a graph and minimum spanning tree algorithms are discussed in this paper. The purpose of this study is to give fundamental details on the spanning trees and related work done based on their application domains. The application domains include computer networks, bio-informatics, image processing etc. It is found that research related to spanning trees can be related to the area of graph mining.